Role of a Precision Biotic Fed to Dekalb White Laying Hens at Peak Production - ElsiAnna Rodewald; Brooke Jasek; Li Zhang; Stacey Roberts; Cristiano Bortoluzzi; Pratima Adhikari (Animals)
The objective of this study was to determine the effects of two levels of a precision biotic (PB) within a reduced CP diet for performance, digestibility, and blood biomarkers in Dekalb White laying hens from 24 to 42 weeks of age. A total of four diets were fed: (1) an industry-standard positive control (PC) diet with a formulated CP level of 17.5%; (2) a negative control (NC) diet with a formulated CP level of 15.5%; (3) NC with 0.5 kg/ton PB (NC+PB1); (4) NC with 0.7 kg/ton PB (NC+PB2). The NC diet decreased hen–day egg production compared to the PC diet, and supplementation with both levels of PB led to intermediate levels of production. There was a similar trend for the feed conversion ratio (FCR), measured in kilograms of feed per dozen eggs. Feed cost was lower in the reduced CP diets compared to the PC. Apparent total tract digestibility was decreased with PB supplementation without differences in apparent ileal digestibility. The increased plasma uric acid levels in the NC+PB2 group suggest a shift in protein metabolism toward higher efficiency in ammonia detoxification. While more research is needed on PB, this research suggests that supplementation with PB in laying hens could potentially improve performance parameters.